2020
DOI: 10.1016/j.micinf.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative computational analysis of SARS-CoV-2 nucleocapsid protein epitopes in taxonomically related coronaviruses

Abstract: publicly funded repositories, such as the WHO COVID database with rights for unrestricted research re-use and analyses in any form or by any means with acknowledgement of the original source. These permissions are granted for free by Elsevier for as long as the COVID-19 resource centre remains active. Microbes and Infection xxx (xxxx) xxx Please cite this article as: B. Tilocca et al., Comparative computational analysis of SARS-CoV-2 nucleocapsid protein epitopes in taxonomically related coronaviruses, Microbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(135 citation statements)
references
References 18 publications
6
128
0
1
Order By: Relevance
“…[ Ahmed et al 2020]. It is worth noting that these epitopes were also considered in another study aiming to provide a molecular structural rationale of the major nucleocapsid protein epitopes for a potential role in conferring protection from SARS-CoV-2 infection [Tilocca et al 2020]. We herein focused on the SARS-CoV-2 N and S proteins because both these two proteins are the main targets of vaccines and antiviral drugs due to their dominant and long-lasting immune response previously reported against SARS-CoV [Ahmed et al 2020.We aligned the homologous protein sequences in the seven human coronaviruses and used the resulting alignment to calculate a conservation profile by using the software Rate4site [Pupko et al 2002] (see Materials and Methods).…”
Section: Identification Of Conserved Epitopes In Spike and Nucleocapsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ Ahmed et al 2020]. It is worth noting that these epitopes were also considered in another study aiming to provide a molecular structural rationale of the major nucleocapsid protein epitopes for a potential role in conferring protection from SARS-CoV-2 infection [Tilocca et al 2020]. We herein focused on the SARS-CoV-2 N and S proteins because both these two proteins are the main targets of vaccines and antiviral drugs due to their dominant and long-lasting immune response previously reported against SARS-CoV [Ahmed et al 2020.We aligned the homologous protein sequences in the seven human coronaviruses and used the resulting alignment to calculate a conservation profile by using the software Rate4site [Pupko et al 2002] (see Materials and Methods).…”
Section: Identification Of Conserved Epitopes In Spike and Nucleocapsmentioning
confidence: 99%
“…The N protein is of potential interest for vaccine development as it is highly immunogenic and its amino acid sequence is highly conserved. This protein contains two structural domains: the N-terminal domain, that acts as a putative RNA binding domain, and a C-terminal domain, which acts as a dimerization domain [Tilocca et al 2020].…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study that identified epitopes in the SARS-CoV-2 N protein found the N protein in pangolin CoV failed to align with two of those epitope sequences. 44 From this, the authors claim separations exist between functional adaptation and molecular evolution. There are variations between NTDs in SARS-CoV-2 and Pangolin-CoV MP789; despite their N proteins having a close evolutionary history.…”
Section: Resultsmentioning
confidence: 99%
“…Given the N protein is immunogenetic, knowing the amino acid and structural differences can be useful for developing antigens in serological detection, antiviral medications, and vaccine candidates. 11,44 In regard to the flexible coils in Pangolin-CoV MP789 and Bat-CoV RaTG13, these features might also be inherent to their respective NTDs. Based on the data used to verify homology models, it seems these features are not errors as each model presented with ideal values for energy and stereochemical quality.…”
Section: Resultsmentioning
confidence: 99%
“…Nucleocapsid protein, with a mass of 50 kDa, is the most abundant macromolecule in coronaviruses and is highly immunogenic [ 52 ]. The comparison of the whole amino acid sequence of chosen N proteins revealed 87.86% similarity between SARS-CoV-2 and pangolin CoV, 90% similarity to SARS-CoV, and 99% similarity to bat CoV [ 52 ]. The nucleocapsid protein of SARS-CoV has the capacity to neutralize the immune response of the host.…”
Section: Differences and Similarities Between Sars-cov And Sars-comentioning
confidence: 99%